Determining Professional Ethics As A Mediator Against Tax Avoidance (Study On Malang Regional Tax Consultant) - Sugiyanti, Sugiyanti; Muawanah, Umi; Adisatya, Kohar (International Journal Labs, 2023)
This study aims to determine and analyze the influence of: 1) ewuh pakewuh culture on professional ethics, 2) professional commitment to professional ethics, 3) professional ethics on tax avoidance, 4) ewuh pakewuh culture on tax avoidance dinediation professional ethics, 5) professional commitment to tax avoidance mediated by professional ethics. Using an explanatory research approach,this research was carried out at the Tax Consultant Office in Malang in June-August 2022. The population is 100 employees of the Consultant. The sample was determined by convenience sampling obtained as many as 81 people. Primary data is obtained by sending questionnaires to respondents through goole form. Once the data is collected, it is analyzed by path analysis. To test the hypothesis used t-test and to determine ethics as a mediator used Sobel test. The results of the study proved that: 1) ewuh pakewuh culture has a significant positive effect on professional ethics, 2) professional commitment has a significant positive effect on professional ethics, 3) professional ethics has a significant positive effect on tax avoidance, 4) professional ethics is able to mediate/increase the influence of ewuh pakewuh culture on tax avoidance, 5) Ethics is able to mediate/increase the influence of professional commitment to tax avoidance.